Visual Branding Strategies For Culinary Msmes In Legok Village: A Community-Centered Approach Through Design Training - Fahmy Rinanda Saputri; Melissa Indah Fianty; Cynthia Sari Dewi (International Journal Of Community Service, 2023)
Community engagement through training in logo and packaging design for culinary MSMEs in Legok Village is an initiative aimed at enhancing the competitiveness and sustainability of micro, small, and medium-sized enterprises (MSMEs) in rural areas. Legok Village, renowned for its traditional culinary richness, is the focal point of this research. This study presents a community-based approach employed to strengthen the visual identity of culinary MSME products through design trainingusing Adobe Ilustrator.The methodology includes phases of identifying the needs of MSMEs, conducting logo and packaging design training, and evaluating the impact of this training. The research findings indicate that logo and packaging design training has a significantly positive impact on the development of culinary MSME products, enhancing their visual appeal, and increasing brand awareness in both local and regional markets.The results have significant implications for the development of culinary MSMEs in similar villages. The improved quality of logo and packaging design benefits MSME businesses and can increase household income, stimulate local economic growth, and enhance the quality of life in rural communities. Thus, community engagement through logo and packaging design training for culinary MSMEs emerges as a crucial instrument in building economic sustainability in rural villages.